Use of lactic acid modified MoS2 nanopetals to improve photocatalytic degradation of organic pollutants. (10th August 2018) - Vattikuti, S V Prabhakar; Nagajyothi, P C; Shim, Jaesool
Abstract: Transition metal dichalcogenide-based molybdenum disulfide (MoS2 ) are currently gaining considerable attention due to their prospective technological applications. Herein, we report a facile and simple one-step preparation of self-assembled two-dimensional MoS2 nanopetals modified with lactic acid (LA@MoS2 ). An investigation of the properties of the synthesized LA@MoS2 nanopetals under different conditions reveals that the weight percentage of lactic acid (LA) significantly influences the structural purity, crystalline quality, and morphology of the products, and the appropriate concentration of LA is the determining factor in the synthesis. Photocatalytic activity of LA@MoS2 nanopetals for organic dye decolorization is examined using crystal violet (CV) and methyl orange (MO). The results showed that LA molecules cover the MoS2 with C–S bonds, which significantly enhance photocatalytic decolorization of CV and MO pollutants under simulated solar light irradiation. The LA@MoS2 demonstrated excellent photocatalytic performance compared to bulk MoS2 . Furthermore, electrochemical studies reveal fast electron and hole pathways for the reduction of pollutant molecules in aqueous solution. These results indicate that LA@MoS2 is a good photocatalyst because of the desirable active species in the modified catalyst.